Monster or Hero?: far-right Responses to Anders Behring Breivik and the July 22, 2011 Terrorist Attacks - Berntzen, Lars Erik (Perspectives on terrorism, 2021)
This study maps and seeks to explain the evolution of far-right responses to the July 22 terrorist attacks in 2011. We identify substantial temporal and spatial variation in how different far-right actors responded between 2011 and 2021. These findings present us with four puzzles: First, why was Breivik rejected by the far right in Western Europe, while receiving substantial support in Russia and eventually also from online subcultures originating in the United States? Second, why did parts of the far right not only reject Breivik, but vehemently condemn him? Third, why did initial support for Breivik in Western Europe come from individuals outside the organized far right? And fourth, why does support for Breivik seem to increase with distance in time and space? We argue that the nature of taboos offers an elegant explanation to these puzzles. We propose that the strength of the macro-cultural taboo against violence provides an overarching explanation, mediated by three taboo-related mechanisms referred to as contagion, rebellion, and decoupling. In regions where the taboo against violence is strong, most future support for right-wing terrorism will probably continue to manifest itself through anonymous online spaces, while the more organized far right will continue distancing itself from taboo violators to avoid becoming (complete) social and political pariahs.